Numerical Modeling of Delamination in GFRP Composites - KHOSHRAVAN, M. R.; YOURDKHANI, A. (Engineering Transactions, 2007)
Polymer matrix composites have become highly relevant structural materials. However, high performance laminates are quite susceptible to transverse cracking and delamination. Transverse cracks may cause significant stiffness losses, accelerate environmentally induced degradation and generate delamination. The characterization and modeling of fracture behavior is thus highly relevant for the design of composite parts. In this paper, the delamination phenomena in the Mixed Mode I+II which is one of the important cause of failure in multilayer composites, are studied. The composite is a GFRP (Glass Fiber Reinforced Plastic) and are studied under static monotonic loading. Using the Irwin–Kies criteria, usual laws of elasticity and VCCT (Virtual Crack Closure Technique), based on finite element method, the SERR (Strain Energy Release Rate) in Mode I, Mode II, and four ratio Modes (GI/GII) are evaluated. The finite element analysis of test bars is carried out using ANSYS5.5 software in two dimensions, and the appropriate boundary conditions are chosen. Our numerical results are compared with known experimental ones and with application of the local effects, such as three-dimensional (3D) effect in the width of the test bar with the shape of MMB (Mixed Mode Bending) specimen, scattering between experimental and numerical results is evaluated and discussed. For the 3D effect, the variation of the stress components in the mid-plane of specimen in which delamination occurs, versus the width of specimen, is obtained. Then the variation of strain energy release rate in different ratio Modes, in the width of test bars is calculated.